Comparative Study on the Distribution of Oil Rents in Bolivia, Colombia, Ecuador and Peru - World Bank (Washington, DC, 2014)
Oil rent accounts for a significant portion of the gross domestic product (GDP), the national budget, and the foreign-exchange revenues in the producing countries of the Sub-Andean Basin. Its availability presents an opportunity and a challenge. The issue of the management and use of the oil rent is generating increasing concern among oil companies, civil society, development agencies, and, governments. The above-mentioned stakeholders agree that oil-producing regions, and in particular people dwelling in such regions, should receive indemnifications for damages resulting from oil operations and should realize the opportunity to enter a development growth path. To accomplish this, the regions and the people must benefit from a part of the rent. The study presents in a systematic way the available information on the distribution of oil rents in the Sub-Andean Basin (Bolivia, Colombia, Ecuador and Peru). Its principal aim is to understand the challenges and risks in the ongoing processes and to identify the trends regarding the rent distribution, in particular, and the fiscal decentralization, in general.